CONCEPTS OF SECULARISM AND RELIGIOSITY AND THEIR SOCIAL IMPORTANCE (American Journal of Pedagogical and Educational Research, 2023)
In the article, the concepts of secularism and religiosity in the process of globalization today, its study by many scientists, thinkers and religious scholars since ancient times, the issues of the negative impact of the processes taking place in the world today, especially in the countries of the Middle East, on the mutual balance between religiosity and secularism are highlighted. shows that it has its influence not only in the Middle East, but also in countries with multi-religious and multi-ethnic populations.